2022
DOI: 10.3390/app12020790
|View full text |Cite
|
Sign up to set email alerts
|

Food Products with High Antioxidant and Antimicrobial Activities and Their Sensory Appreciation

Abstract: (1) Background: The demand for healthy and nutritious food is growing worldwide. Fermented dairy products are highly valued by consumers for their health benefits. Kefir is a fermented dairy product that brings many benefits to the consumer due to its antioxidant, anticancer, antidiabetic, antihypertensive and antimicrobial properties. Extracts from various plants in the form of volatile oils have a beneficial efct on consumer health. their antioxidant and antimicrobial activities were demonstrated. (2) Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Interest in this topic was continued in 2022 and 2023, investigating the effect of peppermint, fennel, and lavender oil on cow’s milk kefir. Figure 2 shows the process of obtaining and encapsulating the volatile oil used by Tita et al [ 82 , 83 , 84 , 85 ].…”
Section: Latest Advances In Food and Dairy Products With Encapsulated...mentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in this topic was continued in 2022 and 2023, investigating the effect of peppermint, fennel, and lavender oil on cow’s milk kefir. Figure 2 shows the process of obtaining and encapsulating the volatile oil used by Tita et al [ 82 , 83 , 84 , 85 ].…”
Section: Latest Advances In Food and Dairy Products With Encapsulated...mentioning
confidence: 99%
“…This resulted in an innovative dairy product with high nutritional value and health benefits for the consumer. Figure 3 shows samples of yoghurt and kefir with encapsulated volatile oil obtained by Tita et al [ 82 , 83 , 84 , 85 ].…”
Section: Latest Advances In Food and Dairy Products With Encapsulated...mentioning
confidence: 99%
See 1 more Smart Citation
“…Tit , a et al [3] used three types of volatile oils, namely, volatile mint oil, volatile fennel oil, and volatile lavender oil to improve the quality of a kefir-type acid dairy product. In both conducted examinations, the finished product enhanced with volatile oils outperformed the control sample.…”
mentioning
confidence: 99%
“…All of these aspects demonstrated that the investigated items are accepted from a sensory point of view in addition to the positive effects they have on the health of the consumer. The investigated product follows current trends because it incorporates bioactive components that are advantageous for the consumer's health [3,4]. Another study sought to evaluate the antibacterial activity of volatile oils and the changes in the chemical composition of kefir enhanced with encapsulated volatile oils by enzymatic techniques.…”
mentioning
confidence: 99%